Internalization of Islamic Values in Developing Students' Actual Morals - Tambak, Syahraini; Hamzah, Hamzah; Sukenti, Desi; Sabdin, Mashitah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to explore the efforts of madrasah teachers to internalize Islamic values in developing students' actual morals. Using case study research by conducting in-depth interviews with 8 madrasah tsanawiyah teachers and analyzing them with data cleaning, transcripts, coding and categorization, and interpretation. This research resulted in: First, duha sunnah and fardhu prayer in congregation, and get used to respect the teacher, to manage the syahwiya power of students, resulting in